Approximations to the Distribution Functions of Theil's K-Class Estimators - Mariano, Roberto S. (Institutional Knowledge at Singapore Management University, 1973)
For fixed sample size N, the distribution functions of the k-class estimators (k non-stochastic) are approximated up to terms whose order of magnitude is 1/Î¼, where Î¼ 2 is what is referred to in the literature as the concentration parameter. Similar results are also given for the double k-class estimators.